Psychometric Analysis of Olweus Bully/Bullied Questionnaire in Spanish - Resett, Santiago (2018)
The purpose of this study was to explore the psychometric properties of the Revised Olweus Bully/Victim Questionnaire for adolescents in Spanish. A convenience sample of 824 and 1756 high school students in Argentina completed the Revised Olweus Bully/Victim Questionnaire, as well as questionnaires measuring peer nominations, cyberbullying, and internalizing and externalizing problems. Exploratory and confirmatory factorial analysis indicated two related dimensions: one related to being bullied and another related to being and aggressor. Cronbach’s Alphas were good. Regarding validity, both subscales suggested construct validity (significant associations with internalizing and externalizing problems) and criterion validity (associations with peer nomination). Also, test re-test reliability was detected. Therefore, results suggest that the Olweus questionnaire has good psychometric properties in Argentina.